ANALISIS KEPUASAN PETANI TERHADAP PELAYANAN PENYULUHDI BADAN PELAKSANA PENYULUHAN DAN KETAHANAN PANGAN KABUPATEN MAGELANG TAHUN 2014 - Endriani Widyastuti; Nur Widiastuti (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2014)
The research was conducted in Magelang Regency which aimed to determine the level of satisfaction of farmers to services of Civil Servant extension workers and Tenaga Harian Lepas-Tenaga Bantu Penyuluh Pertanian (THL-TBPP) in Badan Pelaksana Penyuluhan Dan Ketahanan Pangan (BPPKP) of Magelang Regency.Type of the research is quantitative descriptive analytical approach by using the Servqual method and followed IPA (Importance Performance Analysis) approach. Sampling of villages were randomly selected with purposif random sampling method, sample of farmers were taken by simple random sampling method. The total samples of villages were 50 and total samples of farmers were 200 persons. The results of the research showed that the services of Civil Servants extension workers in BPPKP of Magelang Regency on all dimensions of quality of extension services by farmers has not been satisfactorily assessed . Dimensions that need to be improved as the main priority were Reliability Dimension attributes that were related with mentoring and consultancy marketing of agricultural products and new technological innovations . In the service of THL-TBPP , all dimensions of quality of extension services by farmers has not been satisfactorily assessed. Dimensions that need to be improved as the main priority were Reliability Dimension attributes that were related with mentoring and consultancy marketing of agricultural products and the innovation of new technologies and Assurance Dimension attributes that primarily related to the settlement of the problems of farmers in their farm .